Foliar application of salicylic acid and its impact on pre and post-harvest attributes of Antirrhinum majus L. - Akram , Ahsan; Asghar, Muhammad Adeel; Younis, Adnan; Akbar, Ahmed Faiz; Talha, Muhammad; Farooq, Amjad; Akhtar, Gulzar; Shafiqe, Muhammad; Mushtaq, Muhammad Zaighum (Journal of Pure and Applied Agriculture, 2023)
Antirrhinum (Antirrhinum majus L.) is a popular specialty cut flower worldwide, has high demand and prospective due to its incredible color and species. It is a very stipulating flower on various occasions. A study was accompanied to assess the influence of salicylic acid (SA) on the growth, development, and post-harvest life of antirrhinum. The study was planned according to Randomized Complete Block Design has three replications and four levels of salicylic acid viz. 100 mg L-1 , 300 mg L-1 , 600 mg L-1 , 900 mg L-1 and control treatment were used. The data regarding pre-and post-harvest attributes plant height (cm), plant fresh weight (g), and dry weight (g), number of leaves, leaf area (cm2 ), flower stalk length (cm), flower diameter (mm), leaf total chlorophyll content (SPAD value), membrane stability index (%), solution uptake (ml), flower opening percentage and vase life (days) was recorded according to the standard technique. The collected data were evaluated statistically by using the Statistix 8.1 software. The current investigation results indicated that using 600 mg L-1 salicylic acid concentration significantly enhance the plant height (91.33 cm), plant fresh weight (43.67 g), flower quality (9.17), and salicylic acid at 900 mg L-1 concentration enhance the number of leaves (59.33), flower stalk length (6.17 cm), the total number of florets (35.17), while by using 100 mg L-1 salicylic acid concentration increase in flower opening percentage (57.02 %), leaf relative water content (90.95 %), membrane stability index (108.16 %), solution uptake (40.44 ml) and vase life were (8.75 days). It is concluded that a higher dose of salicylic acid enhances the biomass production but decreases the postharvest life of Antirrhinum cut flowers. The use of lower concentration of salicylic acid enhances the post-harvest life of cut flowers. © 2022 Department of Agricultural Sciences, AIOU